IL-1, IL-6, TNF-α, and MIF in relative adrenal insufficiency in septic shock: a piglet model (Faculty of Medicine Universitas Indonesia, 2020)
BACKGROUND Inflammatory mediators released during septic shock are involved in the mechanism of adrenal insufficiency. This study investigated the role of interleukin (IL)-6, IL-1, tumor necrosis factor (TNF)-α, and macrophage migration inhibitory factor (MIF) in septic shock with relative adrenal insufficiency (RAI). METHODS We conducted a 6-month experimental study in 20 piglets. Following endotoxin administration, their hemodynamics were monitored and blood samples were drawn to test the levels of cytokines IL-1, IL-6, TNF-α, and MIF every 15 min until septic shock onset as well as during a corticotropin stimulation test. Septic shock was managed by administering fluid resuscitation, inotropic drugs, and hydrocortisone. At the end of the study, the piglet models were classified as either RAI or non-RAI. Immunohistochemistry staining was performed on the hypothalamus of the RAI group. RESULTS The level of IL-6 at 45 min was higher in the RAI group than the non-RAI group (p = 0.008), and that of IL-1 was similar in the two groups during septic shock. The RAI group had higher TNF-α levels at 15 min (p = 0.002) and at 30 min (p = 0.007) than the non-RAI group, and the MIF level during septic shock was higher in the RAI group (p = 0.003) than the non-RAI group. CONCLUSIONS Cytokine-induced inflammatory process of adrenal gland reflected in TNF-α level in 15 min and 30 min, IL-6 in 45 min, and MIF in septic shock condition but not in IL-1.